Language Anxiety among English Major Students in a Less Competitive Context - Kittima Tantihachai; Supaphon Charoensuk; Piyapat Chuai-in (Journal of Communication in Scientific Inquiry (JCSI), 2024)
Language anxiety in the classroom is known as one of the negative factors that reduce learners’ proficiency. This study aimed to investigate undergraduate EFL English major students’ language anxiety. The objectives of the study were 1) to explore learners’ language anxiety levels, 2) to find out the relationship between language anxiety and their achievement in foreign language courses, and 3) to investigate sources of language anxiety participants experienced in their language classroom. Ninety-five students of the first year to the fourth year at a small college in the south of Thailand participated in the study. The research instruments applied in the study were FLCAS - the Foreign Language Classroom Anxiety Scale developed by Horwitz et al (1986) and their English grade point average. The results revealed that the majority of participants are at a moderate anxiety level. The low anxious students had higher English GPA. Worrying about failing English class was the major source of anxiety. The findings encourage teachers’ awareness of students’ language anxiety in their language classroom context.